Predicting outcomes in primary spontaneous pneumothorax using air leak measurements. Issue 4 (24th October 2018) - Hallifax, Rob J; Laskawiec-Szkonter, Magda; Rahman, Najib M
Abstract : The initial treatment regime for primary spontaneous pneumothorax (PSP) is generic and non-personalised, often involving a long hospital stay waiting for air leak to cease. This prospective study of 81 patients with PSP, who required drain insertion, captured daily digital air leak measurements and assessed failure of medical management against prespecified criteria. Patients with higher air leak at day 1 or 2 had significantly longer hospital stay. If air leak was ≥100 mL/min on day 1, the adjusted OR of treatment failure was 5.2 (95% CI 1.2 to 22.6, p=0.03), demonstrating that early digital air leak measurements could potentially predict future medical treatment failure. Trial registration number: ISRCTN79151659 .